Efektifitas Metode Mind Mapping dalam Materi Speaking di Politeknik Negeri Balikpapan - Masrul Huda; Elisabeth Milaningrum (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
The aim of this study is to determine the effectiveness of the Mind Mapping Method to improve students' abilities in learning English mainly in Speaking material. The research method used is a qualitative-descriptive approach. Where students of the Tax Accounting Study Program who were taking English 2, totaling 31 people, were the research subjects. This class was chosen because in the Even Semester of the 2021/2022 Academic Year, they received material in the field of Speaking. The data collection method uses several methods, Interview Method, Observation Method, and. Data analysis uses several steps, reducing data, presenting data, and verifying data to draw conclusions. The results of the data analysis are presented in a descriptive form. Based on the results of the research conducted, it can be concluded that (1) a positive trend is shown from the application of the Mind Mapping Method (2) The results of the questionnaire after the implementation of the Mind Mapping Method indicate satisfaction.